ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN BERDASARKAN DIMENSI MUTU PELAYANAN - Hermawan, Fransisca; Widyastuti, Theresia Dian (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
This study was conducted to analyze the factors affecting customer satisfactionand analyze customer satisfactionâs effect on customer loyalty. The customers were beingstudied used the service and repair provided by the motor workshop. Data was collectedby distributing questionnaires to the customers of Motor Workshop âMuas Motorâ thatwas located at Kelurahan Gunung Batu, Bogor. This study successfully collected thedata, with purposive sampling technique, and analyzed 200 samples that were used asprimary data. This study used multiple linear regression testing. The data collectedwere processed and analyzed using SPSS version 20. Anova test result showed that allindependent variables simultaneously had a signfi cant effect on the level of customersatisfaction. T test results indicated that Physical Evidence, Empathy, and RelationalMarketing dimensions of customer satisfaction had a signifi cant and positive effect oncustomer satisfaction. While Reliability, Responsiveness, and Assurance dimensions ofcustomer satisfaction did not have a signifi cant effect on customer satisfaction. Thisstudy also showed that customer satisfaction had a signifi cant and positive effect oncustomer loyalty.